2014
DOI: 10.1038/modpathol.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

The morphological growth patterns of colorectal liver metastases are prognostic for overall survival

Abstract: Colorectal metastases in the liver grow according to three histological patterns: a pushing pattern, a replacement pattern, and a desmoplastic pattern. The objective of the current study was to explore the prognostic significance of these three growth patterns for survival. The study included 217 consecutive patients, liver resected between 2007 and 2011 due to hepatic metastases from colorectal adenocarcinoma. The growth patterns were assessed on archival hematoxylin and eosin-stained tissue sections. In 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 25 publications
8
70
0
Order By: Relevance
“…Brunner et al 21 revealed that a compact growth pattern (confined by a capsule) was associated with both higher R0 rate and improved survival. A similar observation was noted by Nielsen et al 8 who identified an infiltrative growth pattern as an independent predictor of poor survival, whereas favorable prognosis was correlated with a desmoplastic growth pattern, in which a fibrous rim separates the metastasis from the liver parenchyma. It is noteworthy that both studies 8,21 reported that the compact growth pattern (confined by a capsule) was associated with an increased lymphocytic infiltrate at the tumor margin , which is a recognized favorable prognostic factor in colorectal cancer.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Brunner et al 21 revealed that a compact growth pattern (confined by a capsule) was associated with both higher R0 rate and improved survival. A similar observation was noted by Nielsen et al 8 who identified an infiltrative growth pattern as an independent predictor of poor survival, whereas favorable prognosis was correlated with a desmoplastic growth pattern, in which a fibrous rim separates the metastasis from the liver parenchyma. It is noteworthy that both studies 8,21 reported that the compact growth pattern (confined by a capsule) was associated with an increased lymphocytic infiltrate at the tumor margin , which is a recognized favorable prognostic factor in colorectal cancer.…”
Section: Discussionsupporting
confidence: 83%
“…A similar observation was noted by Nielsen et al 8 who identified an infiltrative growth pattern as an independent predictor of poor survival, whereas favorable prognosis was correlated with a desmoplastic growth pattern, in which a fibrous rim separates the metastasis from the liver parenchyma. It is noteworthy that both studies 8,21 reported that the compact growth pattern (confined by a capsule) was associated with an increased lymphocytic infiltrate at the tumor margin , which is a recognized favorable prognostic factor in colorectal cancer. 2225 Thus, a confounding effect can be attributed to the capsule subtype of tumor growth pattern, which was proposed as a mechanical and chemical barrier to local invasion by tumor cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A mix of two or three GPs is categorised as mixed GP. Patients resected for liver metastases with a desmoplastic GP have a superior survival in comparison to patients resected for liver metastases with a pushing, replacement or mixed growth pattern [18,19]. The aim of this study was to investigate the correlation between GP and specific immune-relevant markers in the immediate tumour surroundings, specifically by evaluating the infiltration of macrophages and T cells and the urokinase-type plasminogen activation receptor (uPAR).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data has supported that idea that growth patterns are probably relevant and may explain the link between margins and outcome. 4,5 The debate has certainly not been laid to rest.…”
mentioning
confidence: 99%